Influence of contact wire pre-sag on the dynamics of pantograph–railway catenary - Cho, Yong Hyeon; Lee, Kiwon; Park, Young; Kang, Bubyoung; Kim, Ki-nam (International journal of mechanical sciences, 2010)
Stiffness variations and wave propagation in railway catenaries are the main sources of contact loss between the pantograph and the railway catenary. The pre-sag of a contact wire is sometimes introduced to compensate for the stiffness variation. To include the pre-sag’s influence on the dynamic interaction of the pantograph–catenary, we present a modified single-degree-of-freedom (SDOF) dynamic system with a time-varying stiffness that is based on a simplified model from a previous study. The pantograph–catenary parameters that are related to the optimal pre-sag to minimise variations in the contact force are obtained by solving the equations of the SDOF dynamic system. The amount of optimal pre-sag is determined from parameters such as speed, span length, uplift, and the stiffness variation coefficient. Because wave propagation is not allowed in the SDOF model, we investigate the influence of pre-sag on the dynamic interaction between the pantograph and the catenary by using both SDOF and finite element method (FEM) models. These models show that, by using the optimal pre-sag, we can significantly reduce the variation in the contact force in the medium-speed range, which is near the 1/2 sub-resonance speed. The influence of pre-sag is confirmed by a field test that was performed on a Korean conventional catenary. However, the FEM model shows that in the high-speed range near 300 km h −1, the introduction of the pre-sag can reduce the variation in the contact force slightly only if uplift force subject to the pantograph is large enough to cause slackening in the droppers next to the supports. Otherwise, it does not reduce the variation in the contact force. The FEM also shows that the optimal pre-sag (less than 1/2000 of span length) in the high-speed range is much smaller than that (about 1/1000 of span length) in the medium-speed range.